Questions européennes - Jaquet, Pierre; Pisani-Ferry, Jean; Le Cacheux, Jacques; Atkinson, Tony; Boyer, Robert; Herzog, Philippe; Hel-Telier, Sylvie; Maurice, Joël; Ould Aoudia, Jacques; Tubiana, Laurence (Paris: La Documentation française, 2000)
"rapports par Pierre Jaquet et Jean Pisani-Ferry, Jacques Le Cacheux, Tony Atkinson, Robert Boyer, Philippe Herzog, Sylvie Hel-Telier et Joël Maurice, Jacques Ould Aoudia et Laurence Tubiana Bibliotheek François Vercammen"